Impacto de la aplicación de fibra óptica en la infraestructura tecnológica para la distribución de internet de la Empresa Eternet de la ciudad de Babahoyo. - Moreno Muñoz, Orlando Ernesto (2024)
The research project is titled impact of the application of fiber optics in the technological infrastructure for the distribution of internet of the Eternet company in the city of Babahoyo, which is based on the analysis of adoption of fiber optics in the company, the which is currently managed with radio frequency, offering its customers low-speed internet, limited range and with connection interruptions. Fiber is a technology that has evolved over time, it has replaced many other technologies such as traditional microwave signals, radio frequency and copper-based data cabling, among others. The application of fiber provides consumers with greater speed, better bandwidth, connection stability and capacity in the volume of data transmission, which are fundamental for the economic development of the company, as well as users, bringing with them the satisfaction of both. The headquarters of the Eternet company is located in the city of Babahoyo. It faces challenges in the implementation of fiber and the improvement of technological infrastructure, among which are economic investment and the rural areas of the canton. This investigation will address important topics such as the characteristics of fiber optics, the opinion of customers, and the assessment of the economic resource, conducting an interview directed at one of the suppliers that has already implemented fiber optics in their company, versus Ethernet that is is in the transition of migrating to fiber, recognizing that it is a quality technology resistant to weather interference, with greater coverage and, above all, better positioning in the competitive market.